The future reform of the criminal procedure. Maybe the no case to answer could be introduced? - Hofmański, Piotr (Studia Iuridica Toruniensia, 2021)
The article criticizes the changes to the criminal procedural law in Poland in the years 2016–2020 and proposes to start work on the draft of a completely new Code. It focuses on the possibility of introducing the common law legal institute of no case to answer institution into the Polish procedure, which, on the one hand, would strengthen the procedural guarantees of the accused person, and on the other, could contribute to increasing the effectiveness of the proceedings. The author formulates the boundary conditions that must be met in order for the introduction of the said institution to be possible. The most important of these is the return to the concept of full adversarial evidence proceedings at the trial before the court of first instance.